An early occupational science? A pragmatic interpretation of the ideas of Eleanor Clarke Slagle / ¿Una temprana Ciencia Ocupacional? Una interpretación pragmatista de las ideas de Eleanor Clarke Slagle. Issue 2 (3rd April 2022) - Morrison, Rodolfo
ABSTRACT: In the past decades, pragmatism has been an epistemology that has inspired many occupational scientists to consider it as an interesting and desirable point of view. Attention has been drawn to the way pragmatism was part of occupational therapy's foundations and how, because of different circumstances, it was no longer explicitly mentioned by the founders of that profession. One of those founders was Eleanor Clarke Slagle, who made several major practical and theoretical contributions based on pragmatism. These contributions could be useful in current times but, due to gender biases prevailing in the androcentric paradigm, they were eclipsed by her managerial role. This paper describes the contributions Slagle made to occupational therapy and her connection to important pragmatists in the early 20 th century. It then reviews background information about pragmatism in occupational therapy, as a basis from which to describe some of Slagle's theoretical contributions which are interpreted from pragmatism and could have epistemological interest for occupational scientists. Several theoretical concepts used by occupational science today are consistent with Slagle's bases, including the conceptualizations about habits, occupational balance, the relationship between occupation and health, and the relevance of play during life, among others. Thus, the former could be a contribution to the historization process of occupational science and of the occupational foundations, theories, and concepts to inform the debate about their relationship with occupational theory.